2005
DOI: 10.1128/aem.71.6.2979-2986.2005
|View full text |Cite
|
Sign up to set email alerts
|

Biomass Production and Assimilation of Dissolved Organic Matter by SAR11 Bacteria in the Northwest Atlantic Ocean

Abstract: Members of the SAR11 clade often dominate the composition of marine microbial communities, yet their contribution to biomass production and the flux of dissolved organic matter (DOM) is unclear. In addition, little is known about the specific components of the DOM pool utilized by SAR11 bacteria. To better understand the role of SAR11 bacteria in the flux of DOM, we examined the assimilation of leucine (a measure of biomass production), as well as free amino acids, protein, and glucose, by SAR11 bacteria in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
131
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(149 citation statements)
references
References 32 publications
(49 reference statements)
17
131
0
1
Order By: Relevance
“…Finally, %RP patterns were compared against available literature values for taxon-specific in situ growth rates (Yokakawa et al, 2004;Malmstrom et al, 2005;Allers et al, 2007;Teira et al, 2009;Ferrerra et al, 2011), and results showed that rankings of taxa based on %RP tracked well with rankings based on measures of in situ growth rates ( Figure 1d). Among the 200 top-recruiting reference bins, the percent of sequences identified as ribosomal proteins (%RP hits) within a genome ranged from 0.05% (Candidatus Pelagibacter ubique HTCC1002) to 20.5% (Chryseobacterium gleum ATCC 35910), and showed distinct phylogenetic patterns ( Figure 1c).…”
Section: Active Community Membersmentioning
confidence: 99%
“…Finally, %RP patterns were compared against available literature values for taxon-specific in situ growth rates (Yokakawa et al, 2004;Malmstrom et al, 2005;Allers et al, 2007;Teira et al, 2009;Ferrerra et al, 2011), and results showed that rankings of taxa based on %RP tracked well with rankings based on measures of in situ growth rates ( Figure 1d). Among the 200 top-recruiting reference bins, the percent of sequences identified as ribosomal proteins (%RP hits) within a genome ranged from 0.05% (Candidatus Pelagibacter ubique HTCC1002) to 20.5% (Chryseobacterium gleum ATCC 35910), and showed distinct phylogenetic patterns ( Figure 1c).…”
Section: Active Community Membersmentioning
confidence: 99%
“…This has shown that many such phylotypes occur in both open ocean and coastal environments, but apparently not every phylotype is found everywhere (at least not in the same proportions; Giovannoni & Rappé 2000). For example, it was from clone libraries that the first members of the SAR11 group were identified; these, now named Pelagibacter, comprised at least 16% of total cells in the mesopelagic and up to 50% of bacterioplankton in the surface ocean (Morris et al 2002;Malmstrom et al 2005). Moreover, it has generally been found that easily cultivable phylotypes are frequently not the most abundant members of bacterioplankton, although abundance may in some cases underestimate importance owing to higher turnover rates (Worden et al 2006).…”
Section: Patterns Of Microbial Diversitymentioning
confidence: 99%
“…For example, one SAR11 subgroup reaches peak abundance in surface waters during the summer, whereas another subgroup peaks in the winter . SAR11 bacteria are the most abundant heterotrophs at BATS and are major consumers of dissolve organic compounds (Morris et al, 2002;Malmstrom et al, 2005), whereas Prochlorococcus is the most abundant photoautotroph and a substantial source of dissolved organics (DuRand et al, 2001;Bertilsson et al, 2005). In addition, SAR11 bacteria and Prochlorococcus are both major consumers of small compounds like amino acids and dimethylsulfoniopropionate (DMSP) (Zubkov et al, 2003;Malmstrom et al, 2004;Vila-Costa et al, 2006;Michelou et al, 2007), which are significant sources of C, N and S to marine microbial communities.…”
Section: Temporal Dynamics Of Prochlorococcus Rr Malmstrom Et Almentioning
confidence: 99%